2001
DOI: 10.1128/aac.45.12.3409-3415.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Two Antimitotic Compounds, Pancratistatin and 7-Deoxynarciclasine, against Encephalitozoon intestinalis , a Microsporidium Causing Infections in Humans

Abstract: The antiparasitic effect of a collection of compounds with antimitotic activity has been tested on a mammalian cell line infected with Encephalitozoon intestinalis, a microsporidian causing intestinal and systemic infection in immunocompromised patients. The antiparasitic effect was evaluated by counting the number of parasitophorous vacuoles detected by immunofluorescence. Out of 526 compounds tested, 2 (pancratistatin and 7-deoxynarciclasine) inhibited the infection without affecting the host cell. The 50% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Because of the importance of cyclin-dependent kinase and their regulators in the multiplication and development of eukaryotes, these enzymes represent attractive potential targets for antiparasitic chemotherapy. It was found that pancratistatin and 7-deoxynarciclasine are cyclin kinase inhibitors (Ouarzane-Amara et al 2001). The previous effect may be responsible for the obtained cysticidal activity of P. maritimum in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because of the importance of cyclin-dependent kinase and their regulators in the multiplication and development of eukaryotes, these enzymes represent attractive potential targets for antiparasitic chemotherapy. It was found that pancratistatin and 7-deoxynarciclasine are cyclin kinase inhibitors (Ouarzane-Amara et al 2001). The previous effect may be responsible for the obtained cysticidal activity of P. maritimum in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Alkaloids are the main active constituents in this plant (Berkov et al 2004) which exhibited anti-fungal, anti-malarial, and cytotoxic activities (Sür-Altiner et al 1999;Sener et al 2003;Kaya et al 2010). Pancratistatin, which is the most important metabolite responsible for the therapeutic benefits of this plant, has been shown to have anti-viral, anti-neoplastic (Pandey et al 2005), and antiparasitic effect against Encephalitozoon intestinalis, a microsporidium causing intestinal and systemic infection in immunocompromised patients (Ouarzane-Amara et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…12,14 Powerful antiviral 18 and antiparasitic 19 activities of pancratistatin constitute a related area of promise. Importantly, it has been noted that pancratistatin and 7-deoxypancratistatin are the only known agents (other than an interferon inducer) to show a significant chemotherapeutic efficacy in a Japanese encephalitis virus-infected mouse model.…”
Section: Introduction and Biomedical Significancementioning
confidence: 99%
“…The antiparasitic effect of these compounds has been tested on a mammalian cell line infected with Encephalitozoon intestinalis, a microsporidian causing intestinal and systemic infection in immunocompromised patients. Pancratistatin and lycoricidine inhibited the infection without affecting the host cell with IC 50 values of 0.18 and 0.2 mM, respectively [67].…”
Section: Ii) Isolation and Biological Activitymentioning
confidence: 99%